SOLUSI PENDIDIKAN QUR’ANI TERHADAP KRISIS KEJUJURAN DALAM TRANSAKSI JUAL BELI: SEBUAH KAJIAN TAFSIR MAUDHU'I - Jannah, Aisyatul (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2025)
The crisis of honesty in transactions has become a moral challenge threatening social and economic stability in society. This article aims to analyze the concept of honesty in transactions based on the Qur'an and propose Qur'anic education solutions to combat fraudulent practices. This research employs a thematic exegesis method (tafsir maudhu’i) with a qualitative approach through library research, involving the analysis of Qur'anic verses on honesty, classical exegesis books, and supporting literature. The findings indicate that the Qur'an strongly emphasizes honesty in transactions as a fundamental basis for justice, transparency, and blessings. Verses such as QS. Al-Mutaffifin and QS. Al-Baqarah issue stern warnings against fraudulent practices while highlighting the importance of documenting and witnessing transactions to prevent disputes. In conclusion, Qur'anic education that instills the values of siddiq (honesty) and amanah (trustworthiness) through gradual approaches and practical applications serves as a strategic solution to foster honest character in individuals, positively influencing social morality at large.